2020
DOI: 10.7759/cureus.7060
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Syndrome Among Health Sciences Students in Saudi Arabia: Prevalence and Risk Factors

Abstract: Altalhi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
113
2
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(175 citation statements)
references
References 9 publications
(19 reference statements)
15
113
2
24
Order By: Relevance
“…Based on this score, 94.5% of university students surveyed in this study can be deemed to have CVS. Previous studies on prevalence of CVS among university students in the Eastern Mediterranean region also indicated a high prevalence, with 97.3% prevalence among medical and health sciences students in Saudi Arabia [ 12 ]. It is also estimated that 86% of medical students in Egypt complain of at least one symptom related to CVS [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this score, 94.5% of university students surveyed in this study can be deemed to have CVS. Previous studies on prevalence of CVS among university students in the Eastern Mediterranean region also indicated a high prevalence, with 97.3% prevalence among medical and health sciences students in Saudi Arabia [ 12 ]. It is also estimated that 86% of medical students in Egypt complain of at least one symptom related to CVS [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the students in the current study used DD for more than six hours per day, which has been shown to be one of the risk factors of developing CVS [ 16 - 18 ], especially in contact lens users [ 11 ]. It is of interest to note that a higher percentage of students in this study use DDs for more than six hours compared to students in the region [ 2 , 12 ]. This could be due to lag of accommodation which has been linked to computer use [ 19 , 20 ], in addition to microfluctuations in accommodation observed during use of computer screens [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern was seen in many studies including recently among university students of different colleges in Saudi Arabia with a headache prevalence of 68%. [ 10 ] Unfortunately, no studies assessing the prevalence of headache among the Lebanese population were found in the literature making it an interesting point to explore in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Ajman (United Arab Emirates) and Jeddah (Saudi Arabia), females were more likely to develop asthenopia. [ 2 10 ]…”
Section: Discussionmentioning
confidence: 99%